Disentangling the Brexit vote: The role of economic, social and cultural contexts in explaining the UK's EU referendum vote. (October 2020) - Abreu, Maria; Öner, Özge
A large number of studies have analysed the role of individual and geographical determinants of voting behaviour in the context of the recent EU referendum in the UK, but several questions remain. A key unresolved issue is the extent of the interaction between individual voter characteristics and the geographical context in which they live, with some of the variance in voter preferences previously attributed to individual characteristics potentially being mediated by the geographical context. Space, and the people who live in it, are in continuous interaction, which requires a careful conceptual and empirical treatment of the issues of composition and sorting. We therefore ask to what extent individuals with very similar individual characteristics voted differently in different places. We use data from the British Election Study, along with a non-parametric matching approach, to analyse whether comparable individuals voted differently in areas with particular economic and cultural characteristics. We find that composition effects account for less than half of the observed constituency-level variation in the vote, while the remaining contextual effects are driven almost entirely by cultural factors.